2004
DOI: 10.1021/jp0492366
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Oligo(phenylene−ethynylene) Self-Assembled Monolayers on Gold

Abstract: Vibrationally resonant sum-frequency generation (VR-SFG) and spectroscopic ellipsometry (SE) have been used to characterize self-assembled monolayer films of unsubstituted and mononitro-substituted oligo(phenylene−ethynylene) molecules on vapor-deposited Au substrates. When combined with quantum chemical calculations of the relevant transition moment directions, orientation distributions and electronic excitation spectra are obtained. The orientation distribution from VR-SFG is in good agreement with previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 73 publications
(141 reference statements)
2
69
0
Order By: Relevance
“…Consequently, highly dilute solutions are required to fabricate true monolayers at the air–water interface. The UV/Vis spectrum of OPE2A in solution features one peak at 328 nm with two shoulders at 359 and 380 nm attributable to π–π* electronic transitions 6. 62…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, highly dilute solutions are required to fabricate true monolayers at the air–water interface. The UV/Vis spectrum of OPE2A in solution features one peak at 328 nm with two shoulders at 359 and 380 nm attributable to π–π* electronic transitions 6. 62…”
Section: Resultsmentioning
confidence: 99%
“…The UV/Vis spectrum of OPE2A in solution features one peak at 328 nm with two shoulders at 359 and 380 nm attributable to p-p* electronic transitions. [6,62] A preliminary investigation of the formation of Langmuir films of OPE2A involving both the concentration and the volume of the spreading solution concluded that only solutions of concentration 1 10 À5 m or lower yield reproducible isotherms. Figure 3 shows representative surface pressure versus area per molecule (p-A) isotherms of OPE2A on water (pH 5.9) and basic subphases (NaOH, pH 11.4).…”
Section: Resultsmentioning
confidence: 99%
“…SFG is a coherent process that detects the second-order nonlinear susceptibility of a material. Different components of the susceptibility tensor can be measured by using different polarization combinations of input and output laser beams (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). As shown extensively in the literature (50)(51)(52)(53)(54)(55)(56), different susceptibility components can interfere with each other if some polarization combinations are adopted.…”
Section: Chiral Sfg Vibrational Spectra Of Adsorbed Fibrinogen Obtainmentioning
confidence: 99%
“…By assuming a molecular coordinate system for an antiparallel ␤-sheet as shown in Fig. 4, the SFG hyperpolarizability tensor elements (40,46,74,75) can be written as…”
Section: Direct Detection Of Strong Chiral Spectra From the Tachyplesmentioning
confidence: 99%
“…Tour et al [10] reported the first assembly of a nanocell with disordered arrays of molecules and Au islands, which exhibited reproducible switching behavior and memory effects at room temperature. Major efforts were also performed by Allara and co-workers at Pennsylvania State University, where gold clusters were used instead of discontinuous gold films in addition to extensive work on molecular self-assembly [114]- [119]. An extraordinary set of molecules for molecular circuits has been synthesized, assembled, and measured by Tour and co-workers at Rice [6], [16], [107], [108], [116], [120]- [143]; their suitable selection of molecules has been the actual drive for the development of molecular electronics.…”
Section: State Of the Art On Nanocellsmentioning
confidence: 99%